A quantitative assessment of current practice in diabetes and hypertension services in pharmacies in urban Nepal. - Grishu Shrestha; Deepak Joshi; Parash Mani Sapkota; Sampurna Kakchapati; Bryony Dawkins; Helen Elsey; Shreeman Sharma; Abhigyna Bhattarai; Sushil Chandra Baral (PLoS ONE)
Background Community pharmacies are one of the first contact points for essential health care in Nepal particularly for those living in cities with limited access to primary care. With increasing prevalence of non-communicable diseases there is increasing recognition that pharmacies should be competent and well-equipped to provide basic services for clients with common NCDs. This paper aims to assess the hypertension and diabetes services delivered by pharmacies and their readiness to deliver quality services in Pokhara Metropolitan City (PMC). Methods We identified all pharmacies providing hypertension and diabetes services in the 33 wards of PMC and gained their consent to complete an adapted version of World Health Organization's Service Availability and Readiness Assessment (SARA) and National Health Facility Survey 2015. The adapted tool assessed the characteristics, extent and quality of diabetes and hypertension services provided within the pharmacies. Readiness to deliver hypertension services was assessed across two domains: i) trained human resource and guidelines and ii) available drugs and supplies; with the addition domain of iii) diagnostics for diabetes. Data analysis was conducted using R studio (version 4.3.0). Results A total of 352 private pharmacies were identified in PMC, 94% of which were registered. The main provider of services was a pharmacist with a paramedic background (37%). While all pharmacies were providing provisional, definitive diagnosis and treatment for diabetes and hypertension, few were categorized as 'ready' to deliver appropriate and quality diabetes or hypertension services, with a mean readiness score of 30.7 for diabetes and 32.1 for hypertension. The average score was highest for the essential equipment and supplies domain for diabetes whereas for hypertension services it was comparatively lower. There were no statistically significant differences in service readiness for both diabetes and hypertension between pharmacies with and without paramedics. Conclusion In urban areas, private pharmacies are involved in the management of non-communicable diseases particularly diabetes and hypertension, but they are poorly resourced, with little guidance and training. Given the continued lack of sufficient public primary care services to meet the needs of the growing urban population, comprehensive training to enhance the capacity of pharmacy staff in the management of diabetes and hypertension, aligning with WHO's Package of Essential NCD (PEN) guidelines is needed. Standardized clinical protocols, strengthened regulatory oversight through registration, licensing and continuous monitoring will further support quality service provision.